Ecology Of Nematode of The Genus Haemonchus - Endoparasites of Animals - Makhamadi Abramatov (Zien Journals, 2021)
Currently, 13 species of the considered genus parasitizing the abomasums of ungulate animals have been recorded. The ungulates of the family of Cervidae (1) Antilocapridae (1), Giraffidae (1), Bovidae (12) and Camels (2) were recorded as definitive hosts of this parasite. Individual populations of the Haemonchus species were recorded in Asia, Europe, America, Africa and Australia. Sex ratio in Haemonchus contortus between females and males is 1:5. One female lays from 150 to 10.000 eggs per day.
Keywords: Nematode; Ruminants; Trichostrongylidae; Infection